DESCRIPTION Engaging minors in criminal ACTIVITIES: comparative legal research - Семчук, Наталія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article, the author analyses the regulation of the counteraction against the retraction of minors tothe criminal activity by the example of some post socialistic states. On the basis of the comparative-legalanalyze it sets the number of additions to the article 304 of Criminal Code of Ukraine.